Comparison of Outcome between Drain and No Drain after Elective Laparoscopic Cholecystectomy - Asif Shams, Sheikh Qais Falah, Aftab Alam, Iram Bashir, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Laparoscopic cholecystectomy (LC) has been established as the gold standard treatment for gallstone disease. However, there is a debate regarding the post-operative placement of a drain in LC. Aim: To compare the outcome of patients undergoing placement of drain versus patients without a drain following elective LC. Methodology: A quasi-experimental study was conducted at Mufti Mehmood Memorial Teaching Hospital, Dera Ismail Khan from September 2017 till August 2019. A total of 136 patients of cholelithiasis were randomly allocated to two groups: A (drain placed) and B (no drain placed). Clinical variables such as age, gender, BMI, duration of surgery, duration of hospital stay, vomiting, abdominal fluid collection and wound infection were recorded for all patients in two groups. Results: The mean age of the patients was 38.6±0.2 years. The mean time of surgery in group A was 44.2±10.3 minutes compared to 45.4±10.3 minutes in group B. The mean time of hospital stay in patients of group A was 2.3±1.0 days compared to 2.3±0.9 days in group B. After surgery, 16(23.5%) patients in group A experienced vomiting compared to 22(32.4%) in group B. Seven (10.3%) patients in group A had abdominal fluid collection compared to 12(17.6%) in group B. Moreover, eight (11.8%) patients in group A developed wound infection compared to 11(16.2%) in group B. Conclusion: There is no need to place a subhepatic drain routinely after laparoscopic cholecystectomy in uncomplicated cases.